EFFECT OF VOLUME-TO-EXPOSED-SURFACE RATIO ON TEMPERATURE AND MAXIMUM ALLOWABLE CASTING TEMPERATURE OF MASS CONCRETE - Tasri, Adek (Journal of Applied Engineering Science, 2025)
For mass concrete, it is well known that a high temperature or temperature differential at an early age can lead to cracks. The temperature and temperature differential are determined by several factors, such as the hydration heat, casting temperature, and mass concrete size. In this study, we numerically calculate the effects of mass concrete size, which is considered in the form of volume-to-exposed-surface ratio (V/A), on the temperature and temperature differential of the mass concrete at various casting temperatures. The data from the numerical calculation was then used to obtain the maximum allowable casting temperature as a function of concrete size. The hydration heat required for the numerical calculation was obtained using an adiabatic calorimeter. The study shows that there is a strong relationship between the maximum allowable casting temperature and the concrete dimension in the form of V/A. The Maximum allowable casting temperature versus concrete dimension curve obtain in this work is useful as a complement to the maximum casting temperature rules commonly used in current practical applications that do not consider the size of the concrete. Based on the concrete composition and environment temperature considered in this study, which is commonly used in practical applications in Indonesia, the maximum allowable casting temperature for V/A of 4,5; 3,0 and 1,5 m are found to be 22,2 OC, 27,1 OC,and 41,2 OC, respectively. The study also found that the difference in core and surface temperatures during early age did not cause a significant difference in strength at both locations.